The Concept of Value in the Production of Architectural - لهيب علي الصائغ (Journal of Engineering and Sustainable Development, 2012)
The concept of value is one of the most important measurement concepts for the formulation of formal output and moral achieve understanding and knowledge of man. It also helps to determining the ways of communication with historical standards, by investment, selection and the determinants of a new revolutionary surge is characterized by producing renewable energy which integrate the human with the surrounding environment, and a component of transport within the ideology blades civilized culture in spite of the different frames of reference and community living environment for each vocabulary.The current research is trying to delve into the concept of value from an architectural point of view and through the monitoring of network concepts and fields of knowledge associated with it, that man lives in her dependents for the purpose of system scenarios out a conceptual framework to identify the nature of the concept and contribute in determining the customary standards of private and public variable with an attribute common reference check the axioms of knowledge in relation to the identity of a community is a creative architectural production tools.